Socio-Poiesis: A Theory on Liberation and Suffering : Toward a New Ethics of Shared Creation and Emancipation - Miri, Seyed Javad, (Social Sciences E-Books Online, Collection 2026., 2026)
Socio-Poiesis is a neologism coined to integrate and intersect theory and practice across several branches of the humanities, including social sciences, psychoanalysis, practical wisdom, Eastern philosophies, ethics, household management, and political philosophy. In this theory, there is a significant point of convergence with the ideas of thinkers like Erich Fromm, Adam Schaff, Adam Blaner, Jacob Moreno, Robin George Collingwood, and others.